Copper-Catalyzed Decarboxylative Cycloaddition of Alkynyl Carboxylic Acids and Sodium Azide with Epoxides and Ethers - Danupat Beukeaw (2022)
Copper-catalyzed decarboxylative cycloaddition of alkynyl carboxylic acids and sodium azide with structurally different epoxides and ethers has been reported for the regioselective synthesis of 1,4-disubstituted-1,2,3-triazoles. These one-pot transformations are likely to proceed through a mechanism that involves an in situ generated organic azide intermediate, a decarboxylative formation of copper-alkyne component, and a ring closure to form triazole product. The present three-component protocols offer several advantages including using economic, bench stable and safe azide source, simple and convenient experimental procedures, high product yields, excellent regioselectivity, wide substrate scope and good functional group tolerance, which could promote their potential synthetic applications in many related areas.